Analisis Kebijakan Pemerintah Terkait Ancaman Penggangguran Pasca Kenaikan Inflasi di Kota Bogor - Defen, Defen; Deviana Lie; Febbryan Zhangrinto; Jesty, Jesty; Katherine (Pusat Riset dan Inovasi Nasional, 2023)
Inflation and unemployment are the two main problems in the economy, when inflation increases, the prices of goods and wages do not move at the same pace. high inflation and unemployment have a negative impact on the economy and stability of the country. He also stated that if inflation is high, unemployment will be low. This study uses a sample of inflation and unemployment rates in Bogor City in 2019-2021 based on the Central Statistics Agency. The analytical method used is descriptive analysis. The results of this study are the influence of low unemployment has a positive impact on the economy and workers, unemployment that is too low can push inflation up. But if the government takes steps to curb inflation, it could reduce unemployment and trigger a recession.